Analysis of the Tibial Epiphysis in the Skeletally Immature Knee Using Magnetic Resonance Imaging: An Update of Anatomic Parameters Pertinent to Physeal-Sparing Anterior Cruciate Ligament Reconstruction. Issue 6 (29th June 2016) - Davis, Derik L.; Almardawi, Ranyah; Mitchell, Jason W.
Background: Physeal-sparing anterior cruciate ligament (ACL) reconstruction is being performed increasingly in skeletally immature knees. Purpose: To determine normal values for the maximum oblique length and "safe" physeal-sparing length and their corresponding angular trajectories across the tibial epiphysis on reconstructed magnetic resonance images (MRIs) in children and adolescents. Study Design: Cross-sectional study; Level of evidence, 3. Methods: An electronic search for pediatric knee MR examinations from April 2003 to April 2013 was performed at our institution. A 3-dimensional system viewer was used to measure the maximum oblique length, physeal-sparing length, and their corresponding angular trajectories on reconstructed MRIs. Knees were stratified by age into 2 groups: group 1 consisted of boys <13 years and girls <12 years and group 2 consisted of older boys (13-14 years) and girls (12-14 years). Each cohort was further stratified by sex. Group 1 consisted of 36 knees (mean age, 10.9 years) and group 2 consisted of 59 knees (mean age, 13.6 years). Results: Significant differences existed for the maximum oblique length and its angular trajectory for the younger versus older cohort (22.2 ± 2.7 vs 23.8 ± 2.7 mm, P = .007; 42.0° ± 4.0° vs 39.4° ± 4.2°, P = .003) and for the physeal-sparing length and its angular trajectory (19.4 ± 2.8 vs 21.3 ± 2.9 mm, P = .001; 30.1° ± 4.1° vs 28.2° ± 4.5°, P = .042). In group 2, females had shorter maximal oblique length and physeal-sparing length than boys (22.7 ± 2.3 vs 25.0 ± 2.7 mm, P < .001; 20.3 ± 2.6 vs 22.4 ± 2.9 mm, P = .004). Conclusion: The maximum oblique length across the tibial epiphysis is shorter than previously believed, measuring approximately 22 mm and approximately 24 mm for high- and intermediate-risk knees, respectively. However, "safe" physeal-sparing lengths were only approximately 19 mm and 21 mm for the younger and older cohorts, respectively. The angles corresponding to the maximum and safe lengths are more acute than commonly thought, measuring approximately 40° and 30°, respectively. All prepubescent knees and intermediate-risk females should receive careful attention before ACL reconstruction due to the relative smaller size of their tibial epiphyses. Clinical Relevance: Physeal-sparing ACL reconstruction is gaining acceptance as a surgical option for complete ACL tear in skeletally immature knees. Iatrogenic growth disturbance after violation of an open growth remains a real concern for surgeons tasked with providing operative management for the unstable pediatric knee. Inadvertent iatrogenic growth plate injury to the tibial physis has been shown to occur more commonly than surgeons would intend during physeal-sparing ACL reconstruction.